Risperidone induced pancytopenia: a case report - Alrahili, Nader M. (International Journal of Basic & Clinical Pharmacology, 2021)
There are several case reports on hematological side effects after using antipsychotics in the literature. This case report could be the first case report of pancytopenia where laboratory work showed thrombocytopenia, lymphocytopenia, and neutropenia after using risperidone. It is about 14-year-old female presented with irritable mood and aggression started on Risperidone 0.75 mg every night. A few weeks later she developed frequent and recurrent urinary tract infections and heavy vaginal bleeding that lasted for 5 days and reoccurred twice in the same month. Patient was admitted to internal medicine ward to investigate the cause of bleeding. No signs of splenomegaly, hepatomegaly, or lymph node enlargement were observed. All immunological workup results were negative. Bone morrow showed normal cellularity with granulocytic hyperplasia, suggesting a peripheral cause that was most likely a drug-induced effect. A provisional diagnosis of drug-induced pancytopenia was established. These hematological side effects may make physician to be more careful while prescribing risperidone and to follow the guideline of regular lab work especially CBC.